Effects of Tea Polyphenol Palmitate Existing in the Oil Phase on the Stability of Myofibrillar Protein O/W Emulsion - Jianchao Li; Zongyun Yang; Zhen Li; Ling Wu; Juan Shen; Jinhua Wang; Peng Wang (Foods, 2022)
This study aimed to explore the effect of adding different concentrations (0, 0.01%, 0.03%, and 0.05% (w/w)) of tea polyphenol palmitate (TPP) in the oil phase on the emulsifying properties of 5 and 10 mg/mL myofibrillar protein (MP). Particle size results revealed that the flocculation of droplets increased as TPP concentration increased and that droplets in 5 mg/mL MP emulsions (25–34 μm) were larger than in 10 mg/mL MP emulsions (14–22 μm). The emulsifying activity index of 5 mg/mL MP emulsions decreased with increasing TPP concentration. The micrographs showed that the droplets of MP emulsions exhibited extensive flocculation at TPP concentrations >0.03%. Compared with 5 mg/mL MP emulsions, 10 mg/mL MP emulsions showed better physical stability and reduced flocculation degree, which coincided with lower delta backscattering intensity (ΔBS) and Turbiscan stability index values. The flow properties of emulsions can be successfully depicted by Ostwald–de Waele models (R2 > 0.99). The concentrations of TPP and protein affect the K values of emulsions (p < 0.05). Altogether, increased protein concentration in the continuous phase could improve emulsion stability by increasing viscosity, offsetting the adverse effects of TPP to a certain extent. This study is expected to promote the rational application of TPP in protein emulsion products of high quality and acceptability.